PENGARUH MOTIVASI BELAJAR TERHADAP PRESTASI AKADEMIK: ANALISIS MULTIVARIAT - Putra, Erlangga Ega Ramadhan; Persada, Gilang Dharma; Ridwana, Muhamad Fitra (STKIP Pesisir Selatan, 2026)
This study aims to examine the effects of internal factors, external factors, and family support on students’ learning motivation and its implications for academic achievement. A quantitative research approach was employed using a survey method and analyzed through Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Data were collected from 134 student respondents using structured questionnaires with a Likert scale and analyzed using SmartPLS software. The measurement model evaluation indicates that all indicators meet the criteria of convergent validity, discriminant validity, and construct reliability. The structural model results reveal that external factors and family support have a significant effect on students’ learning motivation, while internal factors do not show a significant influence. Furthermore, learning motivation has a very strong and significant effect on academic achievement. These findings emphasize the crucial role of the learning environment and family support in shaping students’ motivation, which subsequently influences academic performance. Therefore, educational institutions are encouraged to create supportive learning environments and strengthen family involvement to enhance students’ motivation and academic success.